INCREASING AND IMPROVING READING LITERACY. (PIRLS) - Tuxtasinova, Munira Ibragimovna; Abdullayeva, Nozima Erkinovna (INTERNATIONAL CONFERENCES, 2023)
The teacher and student factor is a leader in the preparation for the PIRLS international research program. The teacher equips with theoretical and practical knowledge.